Implementasi Pendidikan Karakter melalui Pembelajaran Bahasa Indonesia di Era Digital: Studi Kasus di SMKS Al-Ishlah Besuki - Nonny Rulisty Putri Sutikno; Siti Seituni; Namira Choirani Fajri; Inyhatul Hosniyah (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2026)
This study aims to analyze the implementation of character education in Indonesian language learning in the digital era, with a case study at SMKS Al-Ishlah Besuki. Specifically, it investigates teachers’ strategies in integrating character values through traditional teaching methods, the challenges encountered, and the potential role of digital media in supporting effective learning. This research employed a qualitative descriptive approach with a case study design. Data were collected through classroom observation, in-depth interviews with teachers and students, and documentation analysis of teaching materials. The data were thematically analyzed through reduction, categorization, and narrative interpretation. The validity of findings was ensured through source triangulation and member checking. The results indicate that students were able to identify several character values from traditional literary texts, particularly Hikayat Abu Nawas and Rumah yang Sempit. The identified values include religious-spiritual (gratitude, patience), motivation/effort (perseverance, responsibility), and social ethics (humility, avoiding arrogance). However, students’ understanding remained mostly at the moral knowing stage, without progressing toward moral feeling or moral action. The study also highlights several challenges: the complexity of traditional literary language, students’ low reading interest, and their preference for short and visual content typical of the digital generation. To address these issues, the integration of digital media such as short videos, posters, and animations is recommended to strengthen the relevance of character values in students’ daily lives. The findings confirm that traditional literature remains a relevant medium for character education, provided it is delivered through adaptive pedagogical strategies aligned with digital-age learners.